Parental burnout : perceived changes during the lockdown, focus on gender and emotional regulation - Cordon, Pauline Béatrice Marie Boutry (2022)
Dissertação apresentada no ISPA – Instituto Universitário para obtenção de grau de Mestre Psicologia Clinica